Real-time Resource Positioning System based on Wireless Sensor Network in Manufacturing Workshop - Shaobo, Li; Jinglei, Qu; Chenglong, Zhang (International Journal of Online and Biomedical Engineering (iJOE), 2017)
Discrete manufacturing enterprise has a complex and varied production process, which causes manufacturing resources have dynamic characteristics. Aiming at the efficient collect and management of manufacturing resource information, improve the enterprise’ intellectualization, a real-time resource positioning system based on wireless sensor network was proposed. Firstly, a perceptual model for resource positioning was designed, which can collect and analysis real-time resources information in the workshop. Meanwhile, the architectural structure of real-time resources positioning system was designed based on wireless sensor network and the resources positioning flow was illustrated. Aiming at the low positioning accuracy caused by electromagnetic interference and obstacle in manufacturing workshop environment, a multi-sensor positioning data fusion algorithm based on fuzzy evidence theory was proposed. Finally, a prototype system is implemented to demonstrate the validity of the method in practice.